Land : how the hunger for ownership shaped the modern world - Winchester, Simon (New York Harper Collin publishers, 2021)
Explores the concept of land ownership and how it has shaped history, examining how people fight over, steward, and occasionally share land, and what humanity's proprietary relationship with land means for the future.
"Land examines in depth how we determine where the land lies, how we acquire it, how we steward it, how and why we fight over it, and, finally, how we can, and on occasion do, come to share it. Ultimately, Winchester confronts the essential questions: who actually owns the world's land, how much of it do we really need, and why does it matter?" -- Inside front jacket flap.
Keywords: Land tenure -- History; Land tenure -- Law and legislation -- History; Land use -- History; Land use -- Law and legislation -- History; World history; Nature -- Effect of human beings on -- History; World history